Analisis Nilai Tambah Ubi Talas Menjadi Kripik dalam Mendukung Ketahanan Pangan di Kecamatan Riung Kabupaten Ngada - Ngaku, Maria Alfonsa; Kaleka, Marten Umbu; Simo, Daniel (Jurnal Agroteknologi (Agronu), 2025)
This study aims to analyze the added value of taro processing into chips as a strategy to strengthen food security in Riung District, Ngada Regency. The method used is a quantitative descriptive approach with added value analysis using the Hayami method. Data were obtained through interviews, observations, and documentation of taro chip business actors and related agencies. The results of the study indicate that taro processing into chips provides significant economic added value with a taro chip added value ratio of 89.31% from the use of 200 kg of raw materials producing 350 Kg. In addition, the development of taro chip businesses can reduce dependence on imported food and become an alternative in supporting food security in the region. Policy support and training are needed for business actors to increase the productivity and competitiveness of taro processed products in local and regional markets. The conclusion with a high added value ratio, the taro processing business into chips in Riung District has proven to be profitable and has the potential to be developed. This business not only increases people's income, but also contributes to supporting food security